Acyl chain selection couples the consumption and synthesis of phosphoinositides. (30th June 2022) - Barneda, David; Janardan, Vishnu; Niewczas, Izabella; Collins, Daniel M; Cosulich, Sabina; Clark, Jonathan; Stephens, Len R; Hawkins, Phillip T
Abstract: Phosphoinositides (PIPn) in mammalian tissues are enriched in the stearoyl/arachidonoyl acyl chain species ("C38:4"), but its functional significance is unclear. We have used metabolic tracers (isotopologues of inositol, glucose and water) to study PIPn synthesis in cell lines in which this enrichment is preserved to differing relative extents. We show that PIs synthesised from glucose are initially enriched in shorter/more saturated acyl chains, but then rapidly remodelled towards the C38:4 species. PIs are also synthesised by a distinct 're‐cycling pathway', which utilises existing precursors and exhibits substantial selectivity for the synthesis of C38:4‐PA and ‐PI. This re‐cycling pathway is rapidly stimulated during receptor activation of phospholipase‐C, both allowing the retention of the C38:4 backbone and the close coupling of PIPn consumption to its resynthesis, thus maintaining pool sizes. These results suggest that one property of the specific acyl chain composition of PIPn is that of a molecular code, to facilitate 'metabolic channelling' from PIP2 to PI via pools of intermediates (DG, PA and CDP‐DG) common to other lipid metabolic pathways. Synopsis: Phosphoinositides have a characteristic acyl chain composition, but the functional relevance of specifying these acyl chains is unclear. Here, mass spectrometry and isotopologue tracing are used to study the provenance of different molecular species of phosphatidylinositol (PI) in mammalian cell lines. Acyl chains of newly synthesised phosphatidylinositol (PI) undergo rapid remodelling that enriches for stearoyl/arachidonoyl species (C38:4). PI can also be synthesised by a "recycling pathway" that selectively converts existing C38:4‐DG into PI. This process maintains C38:4 enrichment. After PLC‐mediated PI cleavage, the recycling pathway channels released C38:4 lipid backbones through heterogenous pools of biosynthetic intermediates which are common to other pathways (DG, PA and CDP‐DG), into new PI synthesis. These results suggest one of the reasons why PI acyl chains have a distinctive composition is to facilitate the close coupling of PI consumption to its re‐synthesis via acyl chain‐dependent metabolic channelling. Abstract : Pathways of phosphatidylinositol synthesis are uncovered to reveal intricate functional adaptation.